Factors of Formation of Financial Behavior Types of Economic Entities - V. V. Maslennikov; A. V. Larionov; M. A. Gagarina (Финансы: теория и практика)
The research is focused on determining the factors influencing the formation of the types of financial behavior of economic entities. Determining the types of economic entities’ financial behavior is necessary for implementing state economic policy measures. The subject of the study is the types of financial behavior reflecting the propensity of an economic entity to perform economic operations. Entities may exhibit active, adaptive, and reactive financial behaviors. The purpose of the work is to determine the key factors that influence the formation of types of financial behavior of economic entities. The study suggests that the formation of financial behavior types is caused by the influence of human, social and financial capital. The formation of financial behavior types is influenced by the basic characteristics associated with age, perception of the external environment, etc. The significance of certain factors is assessed using statistical analysis. The combination of these factors has a different impact on the formation of the type of financial behavior of an economic entity, but they can be significant under certain external conditions related to the economic situation. Because of the significance of individual factors, all economic entities form ‘yadernye’ (core) groups demonstrating a certain type of financial behavior, as well as groups of entities that change the type of financial behavior depending on the influence of the external environment. The change in financial behavior types is associated with a change in the strength of the impact of various factors that need to be considered in the dynamics. Entities with an active type of financial behavior, whose actions transform the external environment and stimulate other categories of entities to commit economic actions, are of significant interest for the analysis. The latter is especially actual for the financial market when entities with a reactive type of behavior under the influence of the information background commit rash actions leading them to financial losses. Based on the available sociological data, the study examines the main factors that lead to the formation of an active type of financial behavior. As a result of the construction of the econometric model, the authors conclude that the amount of available funds, the age of the respondent, the level of professional competence have a significant impact on the formation of an active type of financial behavior.